STRATEGIC DIRECTIONS AND DEVELOPMENT OPPORTUNITIES FOR INTERNATIONAL COMPANIES IN UZBEKISTAN - Rustamova Salomat Erkamovna (European Science Publishing, 2025)
This article explores strategic directions and development opportunities for international companies operating in Uzbekistan, a rapidly growing Central Asian economy. Following significant economic reforms initiated in 2017, Uzbekistan has become increasingly attractive to foreign investors. The article outlines key sectors ripe for investment, including agriculture, energy, manufacturing, information technology, and tourism. It highlights the importance of understanding local market dynamics, forming strategic partnerships, and leveraging government incentives to navigate the investment landscape successfully. Furthermore, the article addresses potential challenges, such as regulatory complexities and infrastructure needs, while emphasizing the value of corporate social responsibility in enhancing brand reputation. By embracing these opportunities, international companies can play a significant role in Uzbekistan's economic transformation.
Keywords: Uzbekistan, international companies, economic reforms, investment opportunities, agriculture, energy, manufacturing, information technology, tourism, strategic partnerships, corporate social responsibility.